Context is Everything: Psychological Data and Consent to Research. (January 2014) - Lidz, Charles; Appelbaum, Paul S.
Abstract Issues associated with consent to clinical trials have attracted considerable attention recently, spurred in part by controversies over alleged inadequacies in the consent process. Professor Jansen's interesting essay is unusual in two ways. First, it raises issues about the conceptualization of one set of problems in informed consent (which Jansen subsumes under the term "therapeutic error") and, more critically, about the methods and the data used to assess them. Second, she is unique in using the findings of academic experimental psychology to critique the empirical findings. This produces a thoughtful and original critique of the process of informed consent to research that, nonetheless, we believe, yields a model that does not reflect the reality of clinical research.